Society 5.0 in Education: Interactive Learning through Digital Media Integration on Teaching Speaking - Fadhillah, Nurul; Siregar, Elsya Alfitri; Lestari, Umi Hasana Pitri; Rahman, Fadhlur; Khalsiah, Khalsiah (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2024)
Advancements in technology are crucial in achieving the goals of Society 5.0. To achieve this goal, teaching-learning process must be equipped to digital media technologies. As mastering speaking skills is considered as the most challenging aspect in language learning, the aim of this research is to investigate the impact of an interactive learning setting on students' engagement and motivation. Equally significant, to identify best practices for integrating digital media into teaching speaking. This study employed a mixed-methods, combining qualitative and quantitative to comprehend and answer the phenomena. Researchers collected the data by using surveys, observation, and speaking tests. Survey responses and test results were summarized using quantitative analysis. While qualitative analysis was used for observation, it was analyzed to identify common themes and insights about the use of digital media to teach speaking skills. The results of observation showed that interactive learning activities improved students' engagement and motivation in learning speaking skills, and the results of the speaking tests proved that the students' speaking skills improved. Survey results showed that using social media (TikTok) as a digital platform for teaching speaking is the best practice for integrating digital media in enhancing speaking skills within the framework of Society 5.0. This study has significant implications for education, especially in terms of incorporating digital technologies into teaching and learning practices. These findings will be useful for educators, policymakers, and institutions looking to improve learning outcomes in the digital age while also adhering to Society 5.0 principles.